Social Environmental Impact on Adolescent Attachment and Peer Relational Competence - Nancy Indala; Anitha J. Menon; Kusanthan Thankain; Sidney O. C. Mwaba (Archives of Current Research International, 2021)
This study aimed at investigating the differences in attachment levels to the caregiver and the differences in interpersonal relational competence between adolescents raised in the home environment and those raised in orphanages. It was hypothesized that adolescents raised in orphanages would be less attached to their caregivers than adolescents raised in the home environment with regard to trust, communication and alienation. It was also hypothesized that adolescents raised in orphanages would have a lower interpersonal relational competence in comparison to adolescents raised in the home environment. Both the adolescents raised in the home environment and the orphanage-raised adolescents were from Lusaka, Zambia. Stratified sampling technique was used to obtain the sample of 97 adolescents, 48 raised in orphanages and 49 raised in the home environment, between the ages 11 and 14 (M=12.27, S.D= 0.94). The Inventory of Parent Peer Attachment (IPPA) was administered to all participants. Significant differences were found between adolescents raised in orphanages and adolescents raised in the home environment with regard to their attachment to their respective caregivers. There were significant differences in trust in their caregivers between the two groups t (97) -3.6, p= 0.05. As hypothesized, there were significant differences in interpersonal relational competence between adolescents raised in orphanages and adolescents raised in the home environment. Finally, a strong positive correlation between attachment to the caregiver and peer relational competence was found between alienation from the caregiver and alienation from peers r (72) .606, p< .01.Attachment bonds between adolescents and caregivers take place regardless of the rearing environment and peers can buffer the effects of harsh rearing environments. More research is needed to better understand the attachment in children under institutional care to stave off negative effects of institutional care in Zambia.